ACCESSIBILITY OF EDUCATIONAL FACILITIES PREDICTOR OF STUDENTS’ ACADEMIC PRODUCTIVITY IN ZONE C SENATORIAL DISTRICT OF BENUE STATE: IMPLICATION FOR SUPEVISION (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study investigated the accessibility of educational facilities as predictor of students’ academic productivity in zone C senatorial district of Benue State: implication for supervision. Two research questions and two hypotheses were used for the study. The study adopted correlational research design. The population of the study consisted of all public secondary school student in zone C senatorial district of Benue State. The simple random sampling technique was used to draw sample from the school. The sample of this study comprises of 240 SS2 students drawn from secondary school in the research area. Data were collected through the use of questionnaire titled (AEFPSAPQ). The statistical tool used for data analysis was Pearson product moment correlation coefficient. The result showed that, there is significant relationship between accessibility of educational facilities such as libraries and classrooms and student academic productivity in the study area. It was recommended among others that facilities such as libraries and classroom should be available for student accessibility which in turns will predict their academic productivity.